2021
DOI: 10.3389/fphar.2021.711701
|View full text |Cite
|
Sign up to set email alerts
|

8-Gingerol Ameliorates Myocardial Fibrosis by Attenuating Reactive Oxygen Species, Apoptosis, and Autophagy via the PI3K/Akt/mTOR Signaling Pathway

Abstract: 8-gingerol (8-Gin) is the series of phenolic substance that is extracted from ginger. Although many studies have revealed that 8-Gin has multiple pharmacological properties, the possible underlying mechanisms of 8-Gin against myocardial fibrosis (MF) remains unclear. The study examined the exact role and potential mechanisms of 8-Gin against isoproterenol (ISO)-induced MF. Male mice were intraperitoneally injected with 8-Gin (10 and 20 mg/kg/d) and concurrently subcutaneously injected with ISO (10 mg/kg/d) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…72 8-Gingerol has also been shown to inhibit myocardial fibrosis by decreasing oxidative stress, autophagy, and apoptosis by regulating the PI3K/Akt/mammalian target of rapamycin (mTOR) signaling pathway. 73 Since PI3/Akt/mTOR axis is critically implicated in PD, 74 this pathway may also underlie the effects of ginger in apoptosis in PD.…”
Section: ■ Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…72 8-Gingerol has also been shown to inhibit myocardial fibrosis by decreasing oxidative stress, autophagy, and apoptosis by regulating the PI3K/Akt/mammalian target of rapamycin (mTOR) signaling pathway. 73 Since PI3/Akt/mTOR axis is critically implicated in PD, 74 this pathway may also underlie the effects of ginger in apoptosis in PD.…”
Section: ■ Future Perspectivesmentioning
confidence: 99%
“…Furthermore, 6-gingerol has been shown to protect against cerebral ischemia/reperfusion injury via the inhibition of apoptosis and through transient receptor potential cation channel subfamily V member 1 (TRPV1)/Fas Associated Factor 1 (FAF1) complex dissociation . 8-Gingerol has also been shown to inhibit myocardial fibrosis by decreasing oxidative stress, autophagy, and apoptosis by regulating the PI3K/Akt/mammalian target of rapamycin (mTOR) signaling pathway . Since PI3/Akt/mTOR axis is critically implicated in PD, this pathway may also underlie the effects of ginger in apoptosis in PD.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It is an antineoplastic agent. It is rich in antioxidants, cardiotonics, and cardioprotective agents, including [8]-gingerol (Xue, et al, 2021b). Inhibition of leukotriene A (4) hydrolase expression and induction of G2/M arrest have been shown to be biochemical mechanisms by which 6-gingerol plays an anti-colorectal cancer role (Kumara et al, 2017).…”
Section: Gingerolsmentioning
confidence: 99%
“…Another study investigated the possible mechanisms by which 8-Gin (10 and 20 mg/kg/d) reduced J-point elevation and heart rate in mice induced with isoproterenol (ISO-10mg/kg/d) for 2 weeks. It was found that 8-Gin exerted cardioprotective effects on ISO-induced MF, which is likely associated with its inhibition of ROS generation, apoptosis, and autophagy by modulating the PI3K/Akt/mTOR signaling pathway (Xue et al, 2021b).…”
Section: In Cardiovascularmentioning
confidence: 99%
“…On the other hand, TGF-β can also regulate the activity of RhoA, promoting the activation of Rho-related kinase (ROCK) and inhibiting cofilin (CFL) [24]. Rac and Cdc42 are also involved in the non-Smad signaling pathway mediated by TGF-β signaling [25][26][27][28][29]. Most notably, TGF-β1 is the strongest profibrotic cytokine discovered to date [30][31][32][33][34]; many studies have shown that blocking the TGF-β1 pathway can improve organ fibrosis [32,35].…”
Section: Introductionmentioning
confidence: 99%